A Computer-Aided Diagnostic System Using a Small Desk-Top Computer-Calculator - Jane, C. Hobeocks (Methods of Information in Medicine, 1974)
This report describes in detail a simple cheap computer-aided diagnosis system based around a WANG 700C desk-top computer/calculator and a WANG 711 input/output writer. Total costs of the system are less than £ 1,000 per anmun. A single diagnosis takes around 3—5 minutes to perform, and the use of the system can be learnt within 30 minutes. Accuracy is of the order of 90% for acute abdominal pain and some degree of flexibility and geographical compatibility has been achieved. Additional problems in implementation are discussed.
Keywords: Computer-aided Diagnosis; Small Computer; Cost-Effectiveness-Analysis